2016
DOI: 10.1089/thy.2016.0062
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Graves' Disease in Relation to Clinical Activity

Abstract: This study demonstrates that different levels of circulating miRNAs are associated with intractable GD. Moreover, serum exosomes of patients with intractable GD may activate immune cells, which may play an important role in GD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 60 publications
3
43
0
1
Order By: Relevance
“…It has been reported that the levels of several cytokines such as IL-4, Il-5, IL-6, IL-8, and IL-12 are altered in patients with active GD [25][26][27][28]. Additionally, we previously revealed that the serum profiles of cytokines and chemokines vary depending on disease activity in patients with GD [2,13,29] ered to depend on the cytokine balance during treatment. The changes in IgG4 levels during GD treatment could be attributed to changes in the cytokine balance.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been reported that the levels of several cytokines such as IL-4, Il-5, IL-6, IL-8, and IL-12 are altered in patients with active GD [25][26][27][28]. Additionally, we previously revealed that the serum profiles of cytokines and chemokines vary depending on disease activity in patients with GD [2,13,29] ered to depend on the cytokine balance during treatment. The changes in IgG4 levels during GD treatment could be attributed to changes in the cytokine balance.…”
Section: Discussionmentioning
confidence: 69%
“…GD is an autoimmune disease characterized by the presence of circulating autoantibodies against the thyroid-stimulating hormone (TSH) receptor. Various factors are involved in GD pathology [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA (2 mg) was reverse-transcribed into cDNA by incubating with deoxynucleoside triphosphate mix (Takara Bio, Kusatsu, Japan), Recombinant RNase Inhibitor (Takara Bio), random primers [hexadeoxyribonucleotide mixture; pd(N)6; Takara Bio], 5X First Strand Buffer (Thermo Fisher Scientific), 100 mM DTT (Thermo Fisher Scientific), and 200 U Moloney Murine Leukemia Virus Reverse Transcriptase (Thermo Fisher Scientific) at 25°C for 10 min, 37°C for 60 min, and then 70°C for 15 min. Finally, the cDNA was used for real-time quantitative PCR (qPCR) reaction (29). qPCR was performed for the quantitative assessment of mRNA expression using an ABI Prism 7900HT Sequence Detection System (Thermo Fisher Scientific) and Thunderbird SYBR qPCR Mix (Toyobo, Osaka, Japan).…”
Section: Quantitative Assessment Of Mrna Expressionmentioning
confidence: 99%
“…Hiratsuka et al used miRNA array to identify circulating miRNAs in relation to disease activity of GD by recruiting seven intractable GD patients, seven GD patients in remission, and seven healthy controls, and found that miR-23b-5p and miR-92a-3p were significantly increased in GD patients achieving remission, but let-7g-3p and miR-339-5p were significantly lower in GD patients achieving remission than intractable GD patients, demonstrating that some miRNAs could be as biomarkers of intractable GD and treatment response (134). A recent study by Li et al found that patients with higher miR-346 level at diagnosis were at a higher risk of relapse during follow-up (125).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%